Step-by-step explanation:
To find the equation, we first need to calculate the slope of the line. So, we can calculate the slope of the equation as follows:
![m=(y_2-y_1)/(x_2-x_1)](https://img.qammunity.org/2023/formulas/mathematics/high-school/78uaqhwt0aws3qfwxigaftpihnmb1gzxtp.png)
Where (x1, y1) and (x2, y2) are two points in the line. So, replacing (x1, y1) by (5, -1) and (x2, y2) by (-5, 2), we get:
![m=(2-(-1))/(-5-5)=(2+1)/(-10)=(3)/(-10)=-(3)/(10)](https://img.qammunity.org/2023/formulas/mathematics/college/sosi9qxlxtbosyudb69sa5c6sutwqk0bzz.png)
Now, the equation of the line can be found as:
![y-y_1=m(x-x_1)](https://img.qammunity.org/2023/formulas/mathematics/high-school/csobd57zth7rh9k4hz9amldzpq2owf0z4j.png)
Then, replacing the slope by -3/10 and (x1, y1) by (5, -1), we get:
![undefined]()